Transformasi Pendidikan Islam untuk Generasi Z: Peran Teknologi dalam Ruang Kelas - Salsabila, Unik Hanifah; Iftakhuzzulfa, Andita; Tsani, Fathi Hana’ ibnu (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
Islamic education has had an important role since the time of the Prophet Muhammad ﷺ until now. Generation Z or the younger generation plays a key role in changing the governance structure in a country. This article discusses the challenges and potential of Islamic education in facing the development of modern technology. Surveys show that generation Z's moral and moral education tends to be neglected, focusing on modern education, and lacking attention to moral values. Islamic religious education is faced with the challenge of utilizing technology effectively so as not to be left behind by western education. This article proposes the integration of technology curriculum in Islamic religious education, the use of educational applications, and paying attention to the impact of the transformation of Islamic education on the character and morals of generation Z. The research method used is library research with a text analysis approach and related information. Data sources involve scientific books, journals, scientific research, case studies, and other related sources of information. As a result, Generation Z has certain characteristics, such as inclusiveness, independence and realism. The use of technology in Islamic religious learning among generation Z shows positive potential, but also faces challenges, such as short attention spans and dependence on teachers. Technology curriculum integration needs to pay attention to learning independence and maintaining religious values. Although positive impacts include creativity and wider access, there are potential negative impacts such as loss of depth of religious understanding and social isolation. Therefore, there needs to be cooperation between educators, government and parents to design a balanced educational strategy in facing the transformation of Islamic education for generation Z.